pH and Redox Dual-Sensitive Covalent Organic Framework Nanocarriers to Resolve the Dilemma Between Extracellular Drug Loading and Intracellular Drug Release - Wang, Chaoyu; Liu, Huiming; Liu, Shuai; Wang, Zhijun; Zhang, Jianhua (Frontiers in Chemistry, 2020)
Cancer poses a serious threat to human health. To enhance the efficacy of tumor chemotherapy, it is urgent to develop novel and effective nanocarriers with the ability to efficiently load and delivery anticancer drugs. Covalent organic frameworks (COF)-based nanocarriers (CONs) have exhibited great potential for drug loading, due to their porous structure and high surface area. However, the function of tumor intracellular-triggered drug release has barely been integrated. Herein we first synthesized a kind of hydrazide and disulfide bonds containing building block (4,4'-Dihydrazide diphenyl disulfide, DHDS), which was used to develop a PEGylated pH and redox dual-sensitive CONs (denoted HY/SS-CONs) for efficiently loading and delivering doxorubicin (DOX). The obtained HY/SS-CONs can achieve a very high loading content of DOX and very low premature leakage at physiological condition. However, under tumor intracellular microenvironment, HY/SS-CONs with acid-cleavable hydrazone bonds and GSH-exchangeable disulfide bonds will undergo rapidly disintegration and efficiently release DOX to kill tumor cells. The COFs-based dual-sensitive nanocarriers provide a promising solution to the dilemma between extracellular drug loading and tumor intracellular drug release.